Nord et Sud : la complexité de leur relation dans Great Trade Route de Ford Madox Ford (1937) - Marine Bernot (Babel: Littératures Plurielles, 2014)
It is commonly believed that the migration of human beings across the globe has always been influenced both by the physical restraints of their kind, and by the weather conditions then available to them. This very observation gave way to various “meteorological climate theories” which claimed to define the Volkgeist of nations, using archetypes and somewhat uncomplimentary standards, based on the sole climatic criterion. Though Ford Madox Ford did partake in this ideology, setting a clear contrast between North and South based on their distinctiveness throughout History, he also believed that a more prosperous relationship was possible; using the ancient Silk Road as a symbol of this symbiosis, which gathered the nations along its curves thanks to barter. Could such an archaic system of exchange be the key to a better world? Could it be the antidote to the new overproductive industrial era which enslaved the Small Producer?